Supervision and containment in community clinic contexts : a study of trainee clinical psychologists' experiences. - Revington, Nicola (My University, 2009)
This study conceptualises the workings of supervision within a South African community clinic setting, focusing specifically on trainees’ experiences of work and supervision in such contexts. Training and working in community contexts has become increasingly important in the field of clinical psychology in South Africa. Multiple and varied challenges face trainees learning and working in these contexts. The experience may evoke overwhelming emotional responses for trainees. Supervision can play an important role in offering support and providing a reflective space for trainees, thus helping to render their experiences manageable and meaningful. A qualitative research design was used in this study to explore the experiences of trainee psychologists learning and working at a community clinic in Johannesburg as a component of their clinical psychology Masters training. Six past clinical psychology trainees from the University of the Witwatersrand were interviewed in order to gain understanding of their experiences of work and supervision from their own perspectives. What emerged from analysis of the interview material was a rich description of the community clinic and the challenges trainees are faced with in working there. The impact of being a new therapist within the environment was an area commonly discussed in interviews. Most significantly, the importance of supervision within the context was highlighted, with interviewees focusing on the need for containment and a space to think. Bearing these ideas in mind, the study draws on psychodynamic theory, particularly that of Wilfred R. Bion, to help conceptualise the workings of supervision in such a context. The study illustrates that considerable and meaningful work and learning can be done in less than ideal circumstances.
Keywords: Supervision; Containment; Trainee clincal psychologists